Virtual Reality in Army Artillery Observer Training - Moreira, Romullo; Oliveira, Jauvane (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2019: Anais do XXI Simpósio de Realidade Virtual e Aumentada, 2019)
The practice of observation in Army Artillery has been hampered by the high cost and the limited number of available instruction areas. Using Virtual Reality (VR) becomes a viable alternative for this important training activity. In this context, was developed the first Brazilian Army VR simulator in which an instructor can train an observer in a virtual environment of Artillery employment. This simulator was tested by a sample of 13 Artillery officers with extensive practical experience in observation. The results were compared with reference values obtained from related work. The data show that the simulator reached the reference values for the two parameters evaluated: presence and effectiveness.